ANALYSIS FACTORS THAT AFFECT STUDENTS' INTENTION OF INVESTING IN CAPITAL MARKET (Case Study towards Students of Faculty of Economics and Business, Universitas Tanjungpura) - Maharani, Cindy Vanessa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
This study aims to analyze the factors that influence student intention in investing in the Capital Market. This research is a quantitative research with survey method. The population of this research is the students of the Faculty of Economics and Business, Universitas Tanjungpura with a total of 99 respondents. The data analysis method used is multiple linear regression. This study uses Investment Intention as the dependent variable. While the independent variables are return, risk, education and knowledge, technological developments, and minimum capital. The results of the analysis and discussion of the research show that return, education and knowledge, as well as technological developments have a positive effect on student investment intention, while risk has a negative effect on student investment intention. Minimum investment capital has no effect on student investment intention.